Instantaneous Achievement of the Hall and Pedersen–Cowling Current Circuits in Northern and Southern Hemispheres During the Geomagnetic Sudden Commencement on 12 May 2021 - Kikuchi, Takashi; Araki, Tohru; Hashimoto, Kumiko K.; Ebihara, Yusuke; Tanaka, Takashi; Nishimura, Yukitoshi; Vichare, Geeta; Sinha, Ashwini K.; Chum, Jaroslav; Hosokawa, Keisuke; Tomizawa, Ichiro; Tanaka, Yoshimasa; et al. (Frontiers in Astronomy and Space Sciences, 2022)
The present paper aims at consistent understanding of observation, theoretical model and simulation with the geomagnetic sudden commencement (SC) observed on 12 May, 2021. The SC in Bx and By, SCx,y, was composed of the positive/negative preliminary (PI) and main impulses (MI) as SCx(+ -) and SCy (- +) in the morning and SCx(- +) and SCy (+ -) in the afternoon at middle latitudes in the northern hemisphere. SCx/SCy in the southern hemisphere has the same/reverse polarity as/to those in the northern hemisphere. The PIx in the northern hemisphere matches the two-cell Hall current vortices with anti-clockwise and clockwise directions in the morning and afternoon, respectively, and the MIx matches reverse Hall current vortices. The PIx and MIx in the southern hemisphere meet the Hall currents that are mirror images of those in the northern hemisphere. The PIy in the northern hemisphere is shown to meet the northward/southward Pedersen currents in the morning/afternoon, and the MIy meets reverse Pedersen currents. The PIy and MIy in the southern hemisphere are found to meet the Pedersen currents that are mirror images of those in the northern hemisphere. At the equator, SCx(- +) is observed, meeting the Cowling currents supplied by the Pedersen currents from the northern and southern hemispheres. The PI and MI electric fields observed by the HF Doppler sounders are westward and eastward, respectively, in both the morning and afternoon, meeting the dusk-to-dawn PI and dawn-to-dusk MI electric fields. The onset of PI is found to be simultaneous with the resolution of a few seconds in both the northern and southern hemispheres, matching the Pedersen-Cowling currents from high latitude to the equator. The instantaneous achievement of the Pedersen-Cowling currents is explained by the TM0/TEM mode wave in the Earth-ionosphere waveguide/transmission line. REPPU (REProduce Plasma Universe) global simulation model reproduces the PI and MI electric fields at middle latitudes and SCx(- +) at the dayside equator, which are consistent with the observations in terms of time scale, direction of electric field and generation of Cowling currents.